2014
DOI: 10.1108/jocm-02-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and post-acquisition performance in transitional economies

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
(93 reference statements)
3
24
0
1
Order By: Relevance
“…Similarly, the relationship between transformational leadership and trust was also found to be significant in Browning's (2014) study of heads of schools in Australia. From a private-sector perspective, Waziri, Ali, and Aliagha (2015) found that transformational leadership is positively related to the adoption of information and communication technology in the construction industry in Nigeria, Yang (2016) found that transformational leadership engendered trust and commitment to change in the insurance sector in Taiwan whilst Babić, Savović, and Domanović (2014) found that transformational leadership is positively related to attitudes toward change in Serbian firms. Yasir et al (2016) found that trust in the leader mediates the relationship between transformational leadership and organisational change capacity in the not-for-profit sector in…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between transformational leadership and trust was also found to be significant in Browning's (2014) study of heads of schools in Australia. From a private-sector perspective, Waziri, Ali, and Aliagha (2015) found that transformational leadership is positively related to the adoption of information and communication technology in the construction industry in Nigeria, Yang (2016) found that transformational leadership engendered trust and commitment to change in the insurance sector in Taiwan whilst Babić, Savović, and Domanović (2014) found that transformational leadership is positively related to attitudes toward change in Serbian firms. Yasir et al (2016) found that trust in the leader mediates the relationship between transformational leadership and organisational change capacity in the not-for-profit sector in…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leaders create a convincing vision and share it with employees. When leaders inspire and encourage employees, and communicate optimistically about the future, employees react to these impulses by generating a positive attitude towards changes (Babić et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the impact of transformational leadership on company performance ( Some studies have examined the relationship between the different dimensions of transformational leadership and performance (Podsakoff, MacKenzie, Moorman & Fetter, 1990;Howell & Avolio, 1993;Nemanich & Keller, 2007;Rafferty & Griffin, 2014;Babić, Savović & Domanović, 2014). L. Nemanich and R. Keller (2007) investigated the influence of transformational leadership on the acceptance of acquisitions, employees' satisfaction and employees' performance.…”
Section: Transformational Leadership and Postacquisition Performancementioning
confidence: 99%
“…Određene studije istraživale su uticaj transformacionog liderstva i performansi preduzeća (Garcia-Morales, LlorensMontes & Verdu-Jover, 2008;. Određene studije istraživale su vezu između različitih dimenzija transformacionog liderstva i performansi (Podsakoff, MacKenzie, Moorman & Fetter, 1990;Howell & Avolio, 1993;Nemanich & Keller, 2007;Rafferty & Griffin, 2014;Babić, Savović & Domanović, 2014). L. Nemanich i R. Keller (2007) istraživali su uticaj transformacionog liderstva na prihvatanje akvizicija, satisfakciju zaposlenih poslom, kao i na performanse zaposlenih.…”
Section: Transformaciono Liderstvo I Postakvizicione Performanseunclassified